Analisis Pengaruh Penggunaan Automatic Inline Sampler Terhadap Kinerja Karyawan dalam Pemahaman Pengoperasian di PT. Pertamina Ru V Terminal Lawe – Lawe - Maulana, Arman; Andrianti, Irma; Syamtinningrum, Maeka Dita Puspa (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT. Pertamina RU V Terminal Lawe - Lawe is a company that has a crude oil storage area with a capacity of 800,000 barrels in 7 tanks and a capacity of 1,000,000 in 2 tanks. This research aims to find out whether employees understand the use of automatic inline samplers and to determine the effect of using automatic inline samplers on employee performance in operations. The results of the calculations of this research using linear regression, namely the Validity Test of variables (X) and (Y), on average obtained a calculated r value > r table 5% (0.05), Reliability Test of the two variables (X) and (Y) shows reliability or fulfillment with variables (X = 0.837) and (Y = 0.890), Normality Test using the Shapiro – Wilk test 0.152 > 0.05, Heteroscedacity Test shows 0.393 > 0.05, Autocorrelation Test shows 1.708, Linearity Test shows that the value is 0.156 > 0.05. The Effect of Using an Automatic Inline Sampler on Employee Performance with the equation Y = 0.188 + 1.014X. with a correlation coefficient of 0.883 and a coefficient of determination of 0.779 or 77.9%. And the t test obtained t count > t table or (t count 10.617 > 1.690 t table).